The Digital and Multimodal Turn in Eid Greetings: Reconfiguring the Meaning of Text in the 2026 Digital Eid al-Fitr Greeting - Puji Laksono; Rochyani Lestiyanawati; Arif Widyantoro (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2026)
This study aims to examine the implications of digital communication in expanding the definition of text from linguistic and cultural studies perspectives, focusing on Eid al-Fitr greetings in 2026 as the object of analysis. Traditionally, text has been understood as a linear linguistic structure centered on verbal elements. However, the rapid development of digital technology has transformed communication practices into multimodal forms that integrate various semiotic resources, including visuals, colour, typography, layout, audio, and animation. This study employs a qualitative approach using Multimodal Discourse Analysis (MDA) to investigate how meaning is constructed through the interaction of these semiotic modes in digital greeting messages. The findings reveal that text can no longer be confined to a purely verbal entity but must be understood as a complex and dynamic semiotic ensemble. Meaning is produced through the orchestration of multiple modes that function simultaneously and interdependently. Visual elements, such as religious symbols, colour schemes, and compositional design, play a dominant role in shaping audience interpretation and emotional engagement, often preceding verbal processing. Additionally, the study highlights the significant role of users within digital ecosystems as active producers (prosumers) who creatively combine semiotic resources to express religious identity, cultural values, and social relationships. Furthermore, digital Eid greetings function not only as religious expressions but also as social practices that maintain and strengthen interpersonal connections in virtual spaces. This transformation indicates a broader paradigm shift in communication, where texts become participatory, multimodal, and context-dependent. Consequently, this study contributes theoretically to the redefinition of text in the digital era and emphasizes the importance of multimodal approaches in analyzing contemporary communication practices.